The rationale for quadrivalent influenza vaccines - Ambrose, Christopher S. (Landes Bioscience, 2012)
Two antigenically distinct lineages of influenza B viruses have circulated globally since 1985. However, licensed trivalent seasonal influenza vaccines contain antigens from only a single influenza B virus and thus provide limited immunity against circulating influenza B strains of the lineage not present in the vaccine. In recent years, predictions about which B lineage will predominate in an upcoming influenza season have been no better than chance alone, correct in only 5 of the 10 seasons from 2001 to 2011. Consequently, seasonal influenza vaccines could be improved by inclusion of influenza B strains of both lineages. The resulting quadrivalent influenza vaccines would allow influenza vaccination campaigns to respond more effectively to current global influenza epidemiology. Manufacturing capacity for seasonal influenza vaccines has increased sufficiently to supply quadrivalent influenza vaccines, and methods to identify the influenza B strains to include in such vaccines are in place. Multiple manufacturers have initiated clinical studies of quadrivalent influenza vaccines. Data from those studies, taken together with epidemiologic data regarding the burden of disease caused by influenza B infections, will determine the safety, effectiveness, and benefit of utilizing quadrivalent vaccines for the prevention of seasonal influenza disease.